Memanfaatkan Algoritma Pemrograman dalam Penyelesaian Soal Matematika Menggunakan Software Maple - Nazwa Salsabila Putri; Yahfizham Yahfizham (Jurnal Elektronika dan Teknik Informatika Terapan ( JENTIK ), 2023)
An algorithm is a structured process or steps to solve a problem. Currently, the development of learning media using technology is growing very rapidly, maple software can help in solving math problems, and the author makes steps in using this maple software. This research uses literature research. The goal is to gain an understanding of how programming algorithms help solve math problems with Maple software.